Veterinary medicines in the environment : from the SETAC Pellston Workshop on Veterinary Medicines in the Environment, Pensacola, Florida, USA, 12-16 February 2006 /: from the SETAC Pellston Workshop on Veterinary Medicines in the Environment, Pensacola, Florida, USA, 12-16 February 2006. ([2009]) - Unknown
No abstract available